Navigating The Vast Seas Of Siwak Or Miswak Scholarship: A Detailed Exploration Of Scopus Publications To Unearth Trends, Patterns, And Future Directions - Nusairah Ramli; Nurul Jannah Abd Rahman; Nadrahtul Huda Misral; Ummu-Hani Abas; Nor Haliza Mat Baharin; Juliana Jumal (SPRINGER, 2024)
Indexed by Scopus